The Influence Of Public Information Systems On Auditors' Performance At KAP M. Lian Dalimunthe Dan Rekan - Abel Desiyanti Manik; Galih Supraja (Future Science, 2023)
The rapid development of public information, the complexity of the nature of audit assignments, and the demands on the quality of financial statement audits require auditors to work in an audit team that is capable of working collaboratively efficiently, and effectively. One way to achieve this is through the empowerment of all public information system-based devices and electronic technology. This research presents test results of the influence of public information systems on auditor performance. The research was conducted by distributing questionnaires to auditors at KAP M. Lian Dalimunthe dan Rekan. The research results show that the information system of the public has a significant positive influence on auditor performance. Results research also found that perceived ease of use and perception of usefulness have a significant positive impact on the use of information systems public among auditors, where the perception of ease of use also influences the perception of usefulness held by auditors in system use. The complexity of the auditor's work also influences it positive implementation public information system technology by auditors.